T Cell Repertoire During Ontogeny and Characteristics in Inflammatory Disorders in Adults and Childhood - Foth, Svenja; Völkel, Sara; Bauersachs, Daniel; Zemlin, Michael; Skevaki, Chrysanthi (Frontiers in Immunology, 2021)
Since the first day of life, a newborn has to deal with various pathogens from the environment. While passive immune protection is provided by diaplacental maternal antibodies, the development of cellular immunity is ongoing. A mature immune system should be able not only to defend against pathogens, but should also be able to differentiate between self- and non-self-antigens. Dysregulation in the development of cellular immunity can lead to severe disorders like immunodeficiency, autoimmunity and chronic inflammation. In this review, we explain the role of T cell immunity in antigen detection and summarize the characteristics of a mature TCR repertoire as well as the current state of knowledge about the development of the TCR repertoire in ontogenesis. In addition, methods of assessments are outlined, with a focus on the advantages and disadvantages of advanced methods such as next generation sequencing. Subsequently, we provide an overview of various disorders occuring in early childhood like immunodeficiencies, autoimmunity, allergic diseases and chronic infections and outline known changes in the TCR repertoire. Finally, we summarize the latest findings and discuss current research gaps as well as potential future developments.